Studi Korelasi Kecemasan Dan Konsep Diri Pada Klien Pemasyarakatan - Ni Made Sintya Noviana Utami; Andhini, Luh Putu Ratih; Pramitya, Anak Agung Istri Mira (Bali International University, 2022)
Abstract Background: The social perception of society towards social (correctional clients) tends to be negative. Not only the community, the correctional clients themselves have doubts about themselves being accepted by the environment, getting a job and a decent life. Purpose: to find out the description of anxiety and self-concept of correctional clients in Denpasar Correctional Institutions and to determine the correlation between and fear of self-concept in correctional clients in Denpasar Correctional Institutions. Methods: The research sample consisted of 26 correctional clients who were selected using purposive sampling which established criteria, such as: age 19-40 years, gender male and female, and a minimum of one year in prison. The questionnaire used is a scale based on Nolen's theory (2007) with a total of 44 statement items and a self-concept scale based on the theory of Calhoun and Acocella (in Nugroho, 2015) as many as 30 statement items. Results: the study found that the significance value was 0.003, this indicates that there is a correlation between anxiety and self-concept in correctional clients at the Denpasar Correctional Institution. The correlation value is -0.553 which indicates the direction of the relationship is negative. Conclusion: Correctional clients in the Denpasar Correctional Center have a low to very low self-concept. Research participants had moderate to very high anxiety. There is a correlation with the self-concept of correctional clients. The higher the public's anxiety, the lower the self-concept. Vice versa, the lower the anxiety of correctional clients, the higher their self-concept. Keywords: Anxiety, Self-Concept, Correctional Institution